Grain refinement and texture evolution during high precision machining of a Ni-based superalloy. Issue 1 (2nd January 2017) - Chen, Yanxia; Yang, Yanqing; Feng, Zongqiang; Huang, Bin; Luo, Xian; Zhao, Guangming
Abstract: The grain refinement and texture evolution in the surface gradient microstructure of a Ni-based superalloy induced by high speed machining was studied in this research. The direct evidence of grain refinement induced by dislocation–twin interaction was revealed and the detailed grain refinement process was summarised as deformation twinning, dislocation-twin reaction, localied thinning of nanotwin lamellae and final fracture. The underlying dislocation–twin interaction mechanism was elucidated from the crystallographic perspective. Using electron backscatter diffraction and precession electron diffraction techniques, a multiscale texture analysis covering undeformed coarse grain region, ultrafine grain region and nanograin region was carried out. The texture evolution with decreasing depth to the machined surface was identified as cube in the bulk interior and a mixture of rotated cube 0 0 1<1 1 0>, cube 1 0 0<0 0 1>, copper 1 1 2<1 1 1 > and Goss 1 1 0<0 0 1> textures in the topmost 1.3-μm-thick nanograin layer. The intrinsic thermomechanical effects of high precision machining are responsible for crystallographic texture transformation.